International roadmap for artificial gravity research. (December 2017) - Clément, Gilles
Abstract In this paper, we summarize the current and future research activities that will determine the requirements for implementing artificial gravity (AG) to mitigate the effects of long duration exposure to microgravity on board exploration class space vehicles. NASA and its international partners have developed an AG roadmap that contains a common set of goals, objectives, and milestones. This roadmap includes both ground-based and space-based projects, and involves human subjects as well as animal and cell models. It provides a framework that facilitates opportunities for collaboration using the full range of AG facilities that are available worldwide, and a forum for space physiologists, crew surgeons, astronauts, vehicle designers, and mission planners to review, evaluate, and discuss the issues of incorporating AG technologies into the vehicle design.